Peranan Taman Kota Dalam Mewujudkan Kota Berkelanjutan Di Perkotaan Tulungagung - Zarotul Agustin; Ibtidatul Arofah Azzahro; Muhammad Agil Fachrudin; Lailatul Badriyah Sari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Sustainable city is highly focused on the quality of life of its people. The perspective of city parks is an important factor that makes us livable, enjoyable and attractive to city dwellers. There are still problems in the maintenance of urban parks in social and environmental aspects that support sustainable urban parks. This problem is exacerbated by the large number of street vendors, the anticipated green open space does not match reality, many park areas are damaged and incomplete, and the lack of lighting areas at night is often misused for immoral activities, causing security problems. There are fewer visitors. The purpose of this study was to determine the motives for visiting, the emotional dimension in green open spaces and residents' satisfaction with city park facilities. According to the results of this study, city parks provide character to a city and enrich the city. If the city park is given a good name and the quality is improved, it is not impossible that the city park will really benefit the local community's economy.